Copper‐Catalyzed Recyclable Synthesis of (Z)‐3‐Alkylideneisoindolinones by Cycloisomerization of 2‐Alkynylbenzamides in Ionic Liquids. Issue 3 (24th January 2017) - Mancuso, Raffaella; Pomelli, Christian S.; Raut, Dnyaneshwar S.; Marino, Nadia; Giofrè, Salvatore V.; Romeo, Roberto; Sartini, Stefania; Chiappe, Cinzia; Gabriele, Bartolo
Abstract: The cycloisomerization of readily available 2‐alkynylbenzamides has been conveniently carried out with CuCl2 as catalyst under basic conditions in 1‐ethyl‐3‐methylimidazolium ethyl sulfate (EmimEtSO4 ) as an unconventional solvent. The process leads to ( Z )‐3‐alkylideneisoindolin‐1‐ones in a chemo‐, regio‐, and stereoselective manner. The catalyst/solvent/base system could be recycled several times without appreciable loss of activity. The structures of representative products, that are, ( Z )‐3‐benzylidene‐2‐phenylisoindolin‐1‐one and ( Z )‐3‐pentylidene‐2‐phenylisoindolin‐1‐one, have been confirmed by X‐ray diffraction analysis, and DFT (density functional theory) calculations have been carried out to clarify the roles exerted by the base and CuCl2 in favoring the reaction course leading to ( Z )‐3‐alkylideneisoindolinones. Abstract : The first example of the synthesis of ( Z )‐3‐alkylideneisoindolinones by cycloisomerization of 2‐alkynylbenzamides in ionic liquids is reported. Under the promotion by CuCl2 as simple and inexpensive catalyst, in the presence of K2 CO3 as base, and in 1‐ethyl‐3‐methylimidazolium ethyl sulfate (EmimEtSO4 ) as the solvent, a series of ( Z )‐3‐alkylideneisoindolinones were chemo‐, regio‐, and stereoselectively obtained in high yields, and the catalyst/solvent/base system could be recycled several times without appreciable loss of activity. DFT calculations confirmed the roles exerted by the base and CuCl2 in favoring the anti ‐5‐ exo ‐ dig reaction course leading to ( Z )‐3‐alkylideneisoindolinones.